1999
DOI: 10.1046/j.1464-5491.1999.00201.x
|View full text |Cite
|
Sign up to set email alerts
|

Poorly controlled elderly Type 2 diabetic patients: the effects of increasing sulphonylurea dosages or adding metformin

Abstract: These results suggest that either high sulphonylurea dosages or a therapy combining lower sulphonylurea dosages with metformin are effective and safe in an aged but healthy population. Metformin provides additional benefits counteracting several cardiovascular risk factors but must be administered with caution, bearing in mind the general contra-indications for the drug but not age alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 22 publications
2
20
0
4
Order By: Relevance
“…Potentially favourable effects on blood lipid concentrations and haemostatic activity have also been reported [21], and weight gain may be minimized in obese subjects [21]. In metabolic terms, metformin appears to be safe even in older subjects in whom it has traditionally been avoided [21], and no biological mechanism has been suggested for a potential adverse effect on mortality. The long-term use of combinations of oral hypoglycaemic drugs has been evaluated in several previous non-randomized studies [5].…”
Section: Discussionmentioning
confidence: 99%
“…Potentially favourable effects on blood lipid concentrations and haemostatic activity have also been reported [21], and weight gain may be minimized in obese subjects [21]. In metabolic terms, metformin appears to be safe even in older subjects in whom it has traditionally been avoided [21], and no biological mechanism has been suggested for a potential adverse effect on mortality. The long-term use of combinations of oral hypoglycaemic drugs has been evaluated in several previous non-randomized studies [5].…”
Section: Discussionmentioning
confidence: 99%
“…Metformin decreases circulating concentrations of coagulation factor VII, and may also reduce levels of factor XIII, resulting in decreased crosslinking of fibrin and affecting the structure of the clot [85,86]. Additionally, metformin is known to decrease the sensitivity of platelets to aggregating agents [73,87], consistent with evidence of reduced levels of platelet factor 4 and beta-thromboglobulin [88]. As further evidence of the anti-thrombotic action of metformin, several preclinical experiments have demonstrated that metformin can decrease the formation of artificially-induced thrombi [89,90].…”
Section: Anti-thrombotic Effects Of Metforminmentioning
confidence: 92%
“…90 Other antithrombotic mechanisms of metformin include stabilisation of reduced aggregation of platelets in response to stimuli 90 and reduction of the activity of clotting Factor VII 91 and Factor XIII, 92 which are involved in thrombus formation and stabilisation, respectively.…”
Section: Adipositymentioning
confidence: 99%